Long-term gastrointestinal symptoms and sleep quality sequelae in adolescents after COVID-19: a retrospective study - Yang, Wei-Lin; Wang, Qi; Wang, Ying; Sun, Shaopeng; Shen, Yan; Yu, Lei-Min (Frontiers in Public Health, 2024)
Objective To evaluate the long-term gastrointestinal (GI) symptoms and sleep quality sequelae in adolescents with COVID-19. Methods Between June and July 2023, an online survey was done in Xiaoshan District, Hangzhou City, Zhejiang Province, China, using the GI Symptom Rating Scale (GSRS) and the Pittsburgh Sleep Quality Inventory (PSQI). Results GI symptoms in COVID-19 patients increased by 11.86% compared to before infection, while sleep quality decreased by 10.9%. Over time, there was a significant increase in the cumulative incidence rate of GI symptoms and sleep disorders (p < 0.001). Follow-up of COVID-19 positive patients within 6 months of infection showed that GI symptoms and sleep quality began to ease starting from the first month after infection. Further analysis indicated a significant linear relationship between the severity of GI symptoms and sleep quality (R > 0.5, p < 0.001). Moreover, females, older age, and higher education were identified as risk factors influencing the long-term effects of COVID-19. Conclusion SARS-CoV-2 affects GI symptoms and sleep quality in adolescents during both the acute phase and post-infection periods. Over time, these symptoms gradually alleviate. A significant correlation exists between GI symptoms and sleep quality.